40 is the correct answer. Hope this helps :)
Answer:
-3
Step-by-step explanation:
We want (n/p)(1). We can obtain this by finding n(1) and p(1) and then dividing as indicated:
p(1) = 3(1) - 2 = 1
n(1) = 2(1) - 5 = -3
Then (n/p) (1) = -3/1, or just -3
Correct Answer:
Option A
Solution:
f(x) = 7x + 9
g(x) = 7x - 4
We can re-write g(x) as:
g(x) = 7x + 9 - 13
Since 7x+9 is equal to f(x), we can write:
g(x) = f(x) - 13
This relation shows that g(x) is obtained by shifting f(x) 13 units vertically down. So the correct answer is option A.
Answer:
2 • (2x - 3) • (3x - 2)
Step-by-step explanation: